2017
DOI: 10.1007/s10792-017-0718-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary retinal nerve fiber layer thickness in preeclampsia and eclampsia

Abstract: In relation to the time of pregnancy, peripapillary RNFL reduced in preeclamptic and eclamptic cases as well as in normotensive pregnant women at 2 months postpartum. This reduction was more in the severe forms of pregnancy-induced hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…They suggested that progressive RNFL atrophy and/or pregnancy-induced edema recovery may contribute to the formation of lower RNFL thickness. 2 We demonstrated that PPRNFL mean and superior values were significantly thicker in HPWG than in NPWG and there was no significant difference in the preeclamptic group before and after delivery in our study.…”
Section: Discussioncontrasting
confidence: 38%
“…They suggested that progressive RNFL atrophy and/or pregnancy-induced edema recovery may contribute to the formation of lower RNFL thickness. 2 We demonstrated that PPRNFL mean and superior values were significantly thicker in HPWG than in NPWG and there was no significant difference in the preeclamptic group before and after delivery in our study.…”
Section: Discussioncontrasting
confidence: 38%
“…They speculated that RNFL thickening in patients with preeclampsia might reflect subclinical involvement of the central nervous system [19]. Arab et al reported that the peripapillary RNFL was reduced in women with preeclampsia and eclampsia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Kara et al [56] stated that the RNFL thickness of PE patients was lower than that of normal pregnant women. Arab et al [57] found that women with sPE or eclampsia had the greatest decrease in the average RNFL thickness around the optic disc. erefore, it can be inferred that elevated blood pressure causes irreversible damage to the microstructure of the retina, even though there are no obvious clinical macroscopic symptoms.…”
Section: Hypertensive Retinopathymentioning
confidence: 99%